Hugger mugger - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Spenser novel., 2001)
Boston private detective Spenser journeys to Georgia to protect a young horse after he is hired by Walter Clive, the president of Three Fillies Stables, to uncover the creep who is threatening his prize horse, Hugger Mugger.